في تحليل ربحية الزبائن (ABCII)استخدام نظام الكلفة على أساس المواصفات : لإنتاج الكاشي (X)بالتطبيق على معمل - فائق مال الله محمود; زينة فتحي محمد (PROSPECTIVE RESEARCHES, 2023)
The main element of power in the Attribute Based Costing System (ABCII) lies in its ability to offer products with different specifications for different customers according to their needs and desires. Consequently it has a significant impact on product design process, the cost and marketing. However, the different product specifications required by each customer lead to different profitability generated from each customer. Hence, companies try to analyze customers’ profitability to meet the challenges of the market and maintain the customers who achieve profitability for the company and try to reduce the products cost required by customers who do not achieve profitability for the company. The current research deals with the concept of Attribute Based Costing System (ABCII) in order to analyze the profitability of customers and its contribution in the provision of information on cost required specifications of products by each customer as well as the revenue that can be realized from those specifications. The results show how effective is the Attribute Based Costing System (ABCII) in customer profitability analysis.